Physical Exercise: An Overview of Benefits From Psychological Level to Genetics and Beyond - Wang, Yucong; Ashokan, Kalaiselvan (Frontiers in Physiology, 2021)
Any form of physical activity including exercise is linked with preventing several diseases including metabolic disorders, cancer, and mood disorders. Beyond benefits, its therapeutic activity is inconclusive in terms of types, intensity, and individual training status, and this could be major research for prescribing exercise as therapeutic strategy. Exercise and its myriad forms occupy the space on clinical recommendation, which implies that quantifiable benefits of the same have been proven. Further, the benefits of exercise and its impact have also been found to have a genetic underlying interaction, which has created a niche of personal genomics, wherein apart from diet, an exercise regimen also becomes tailorable for every individual. Many subjective well-being reports highlighted daily exercise to keep mental and general health in excellent conditions, and the uncertainties around it. Thus, adopting an exercise behavior and inculcating it as a routine has been recommended. Further, the kind of benefit that can be extracted out of exercise and training is to a great extent influenced by genetic markers around fat, obesity, hunger, as well as satiety. Genetic markers can also impact the body temperature during exercise, making the entire experience of training either comfortable or unpleasant. Thus, there is overwhelming amount of scientific evidence which have gathered around the benefits of exercise, which became a pressing need from the twenty-first century when the belief on the value of exercise started waning, and that spiked up the era of lifestyle and non-communicable ailments.